Using generative artificial intelligence - Kulyabov, Dmitry S.; Sevastianov, Leonid A. (Discrete and continuous models and applied computational science, 2025)
The use of generative artificial intelligence (GenAI) in scientific publications requires strict guidelines to ensure transparency, credibility, and ethics of research.